Editors’ Responsibility for Publishing High-Quality Research Results: A Worldwide Study Into Current Challenges in Quality Assessment Processes - Krapež, Katarina (LeXonomica, 2022)
The contemporary scientific community faces significant challenges in assuring research credibility. Since the onset of the COVID-19 pandemic, there has been an even greater interest in swift publications of valid research results, and individual editors of reputable academic journals might feel pressured to ensure high quality of published papers. Aiming to explore how editors perceive their management of the quality assessment processes and to identify decisions and processes which editors believe to be the most critical for securing high-quality publications, we conducted a qualitative survey. 258 editors of scientific journals from 42 countries participated in the study. Key findings of the first part of the study show that across disciplines, editors perceived the manuscripts as excellent if they were innovative, scientifically sound, well-written and well-argued, addressed a significant topic, contained useful results, and had the potential to change (improve) something. Secondly, originality emerged as the leading quality criteria in manuscript quality assessment, followed by validity and significance. Finally, results indicate that factors influencing the overall complexity of editorial quality assessment are: (i) clearly defined minimum threshold of required quality, (ii) consistency of assessment between individual quality criteria, and (iii) experience of the editor. Povzetek. Sodobna znanstvena skupnost se pri zagotavljanju verodostojnosti raziskav sooča z velikimi izzivi. Od začetka pandemije COVID-19 se je še povečalo zanimanje za hitre objave veljavnih rezultatov raziskav, posamezni uredniki uglednih akademskih revij pa se lahko počutijo pod pritiskom, da zagotovijo visoko kakovost objavljenih člankov. S ciljem raziskati, kako uredniki zaznavajo svoje upravljanje postopkov ocenjevanja kakovosti ter opredeliti odločitve in postopke, ki so po mnenju urednikov najpomembnejši za zagotavljanje visokokakovostnih objav, smo izvedli kvalitativno raziskavo. V raziskavi je sodelovalo 258 urednikov znanstvenih revij iz 42 držav. Ključne ugotovitve prvega dela študije kažejo, da so uredniki na različnih področjih dojemali rokopise kot odlične, če so bili inovativni, znanstveno utemeljeni, dobro napisani in argumentirani, če so obravnavali pomembno temo, vsebovali uporabne rezultate in imeli potencial, da nekaj spremenijo (izboljšajo). Drugič, izvirnost se je izkazala kot vodilno merilo kakovosti pri ocenjevanju kakovosti rokopisa, sledita pa mu veljavnost in pomembnost. Nazadnje rezultati kažejo, da so dejavniki, ki vplivajo na splošno zahtevnost ocenjevanja kakovosti uredniškega dela, naslednji: (i) jasno opredeljen najnižji prag zahtevane kakovosti, (ii) doslednost ocenjevanja med posameznimi merili kakovosti in (iii) izkušnje urednika.